THE INFLUENCE OF CAPITAL INTENSITY, COMPANY SIZE AND LEVERAGE ON TAX AVOIDANCE IN COMPANIES AUTOMOTIVE SUB SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD 2018-2020 - Chudri, Intan Rizkia; Irmawati, Irmawati; Yusliana, Yusliana; Mauliansyah, Hendri; Dinata, Fendi (IAIN Lhokseumawe, 2023)
The Automotive Sub Sector Company is one of the industrial sub sector companies listed on the Indonesian Stock Exchange which is increasingly growing and developing in Indonesia. This can be seen from the large number of automotive products used both in type and quantity. Apart from product developments, demand for automotive products in society is also increasing, accompanied by population growth. The aim of this research is to examine the influence of capital intensity, company size and leverage on tax avoidance in automotive sub-sector companies listed on the Indonesia Stock Exchange. The type of research is quantitative methods. The population in this study was 36 samples of automotive sub-sector companies listed on the Indonesia Stock Exchange. The object of this research is the automotive sub-sector companies listed on the Indonesia Stock Exchange (BEI). The data analysis technique in this research uses multiple linear regression analysis. The type of data used in this research is secondary data. The research results show that capital intensity, company size and leverage have a positive effect on Tax Avoidance in Automotive Sub-Sector companies listed on the Indonesia Stock Exchange, both simultaneously and partially.